Cancer Burden Variations and Convergences in Globalization: A Comparative Study on the Tracheal, Bronchus, and Lung (TBL) and Liver Cancer Burdens Among WHO Regions from 1990 to 2019 - Mengwei Zhang; Weiqiu Jin; Yu Tian; Hongda Zhu; Ningyuan Zou; Yunxuan Jia; Long Jiang; Jia Huang; Yingjie Hu; Qingquan Luo (Springer, 2023)
Abstract Lung cancer and liver cancer are the leading and third causes of cancer death, respectively. Both lung and liver cancer are with clear major risk factors. A thorough understanding of their burdens in the context of globalization, especially the convergences and variations among WHO regions, is useful in precision cancer prevention worldwide and understanding the changing epidemiological trends with the expanding globalization. The Global Burden of Disease (GBD) and WHO Global Health Observatory (GHO) database were analyzed to evaluate the burden metrics and risk factors of trachea, bronchus, and lung (TBL) cancer and liver cancer. Western Pacific Region (WPR) had the highest age-standardized incidence rate (ASIR) for both liver cancer (11.02 [9.62-12.61] per 100,000 population) and TBL cancer (38.82 [33.63-44.04] per 100,000 population) in 2019. Disability-adjusted life years (DALYs) for liver and TBL cancer elevated with the increasing sociodemographic index (SDI) level, except for liver cancer in WPR and TBL cancer in European Region (EUR). Region of the Americas (AMR) showed the biggest upward trends of liver cancer age-standardized rates (ASRs), as well as the biggest downward trends of TBL cancer ASRs, followed by Eastern Mediterranean Region (EMR). Alcohol use and smoking were the leading cause of liver and TBL cancer death in most WHO regions. Variances of ASRs for liver and TBL cancer among WHO memberships have been decreasing during the past decade. The homogenization and convergence of cancer burdens were also demonstrated in different agegroups and sexes and in the evolution of associated risk factors and etiology. In conclusion, our study reflects the variations and convergences in the liver and lung cancer burdens among the WHO regions with the developing globalization, which suggests that we need to be acutely aware of the global homogeneity of the disease burden that accompanies increasing globalization, including the global convergences in various populations, risk factors, and burden metrics. Graphical Abstract